2021
DOI: 10.3389/fimmu.2021.691590
|View full text |Cite
|
Sign up to set email alerts
|

Arctigenin Exerts Neuroprotective Effect by Ameliorating Cortical Activities in Experimental Autoimmune Encephalomyelitis In Vivo

Abstract: Multiple sclerosis (MS) is a chronic disease in the central nervous system (CNS), characterized by inflammatory cells that invade into the brain and the spinal cord. Among a bulk of different MS models, the most widely used and best understood rodent model is experimental autoimmune encephalomyelitis (EAE). Arctigenin, a botanical extract from Arctium lappa, is reported to exhibit pharmacological properties, including anti-inflammation and neuroprotection. However, the effects of arctigenin on neural activity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 55 publications
1
3
0
Order By: Relevance
“…This is in sharp contrast to findings in early states of neurological disorders, such as Alzheimer's Disease, Multiple Sclerosis and Huntington's Disease. Here, we and others reported firstly a shift towards hyperactivity [17][18][19][20][21][22] . Secondly, this dysregulation was limited to a subset of excitatory neurons exhibiting an increased firing rate.…”
Section: Distinct Functional Microarchitecture Characterized By Low-a...supporting
confidence: 54%
“…This is in sharp contrast to findings in early states of neurological disorders, such as Alzheimer's Disease, Multiple Sclerosis and Huntington's Disease. Here, we and others reported firstly a shift towards hyperactivity [17][18][19][20][21][22] . Secondly, this dysregulation was limited to a subset of excitatory neurons exhibiting an increased firing rate.…”
Section: Distinct Functional Microarchitecture Characterized By Low-a...supporting
confidence: 54%
“…ZINC000013462928 is structurally similar to arctigenin and matairesinol with scores of 0.632 and 0.626, respectively. Both arctigenin and matairesinol have been reported to have neuroprotective, anti-diabetic and anti-depressive activities [ 134 , 135 , 136 ]. The predicted biological activities of the shortlisted compounds corroborate their potential anti-ADAR2 activity.…”
Section: Resultsmentioning
confidence: 99%
“…Its neuroprotective effects have been shown in primary cultures of rat cortical neurons 35 . A recent study reported a reversal of the abnormally high frequency of AMPA-mediated spontaneous excitatory postsynaptic currents to normal levels after ATG treatment 38 . Given the importance of AMPA and kainate receptors in the pathophysiology of many neurological disorders, we investigated whether ATG, TGN and MAT affect the electrically evoked field potentials of the rat CA1 hippocampus and neocortex ex vivo .…”
Section: Discussionmentioning
confidence: 99%